The Serious Naturalist and the Frivolous Collector: Convergent and Divergent Approaches to Nature in D’Amboinsche Rariteitkamer - van de Roemer, Gijsbert M. (Early Modern Low Countries, 2019)
The traditional literature on D’Amboinsche Rariteitkamer depicts a difference between the editor of the text and images, Simon Schijnvoet (1652-1727), and the original author, Georg Everhard Rumphius (1627-1702). Schijnvoet was seen as the ‘frivolous collector’ who did not understand the motives of the original author, whereas Rumphius was seen as the ‘serious naturalist’ and biologist avant la lettre, whose work predated Linnaeus. This paper re-evaluates these contrasting views by placing both men against a broader background of a ‘scientific culture’ and ‘knowledge production’, that was in part informed by the practice of collecting. By discussing their views on the classification of specimens, the formation of specific stones, and the locality of fossilised shells, questions emerge about Rumphius’s modernity and Schijnvoet’s alleged indifference. Even though their opinions often diverged, it will be shown that the motives and interests of the two men were not that different.